Konstruksi Pertentangan Norma Hukum dalam Skema Pengujian Undang-Undang - Lailam, Tanto (Mahkamah Konstitusi Republik Indonesia, 2014)
The study elaborated on the construction of “conflict of legal norms” in constitutional review scheme. There are eleven problems as result of this study, which include: The ideology of the state “Pancasila” as a standard review of “conflict of legal norms” act against 1945 constitution; Constitutional court has a review of act passed before and after 1945 Constitution amendment with standard of 1945 constitution; 1945 constitution is “the living constitution” for the enforcing of law and justice; Constitutional court has authority to review of act against 1945 constitution by vertical and horizontal perspective; enforceability aspect of constitutional review is a part of material review, not formal review; the meaning of “conflict of legal norms” must be comprehend elaborated in the decisions to enforcing of law and justice; Constitutional Court does not used priority of the original intent interpretation and remained unfulfilled of other model interpretation if original intent interpretation caused ineffectiveness of constitution; non constitution be permitted for the formal review, but in material review is not implement; “nemo judex idoneus in propria causa” of procedural law principle can remained unfulfilled by “ius curia novit” principle to promote of the 1945 constitution; the formal review of “conflict of legal norms” can remained unfulfilled by utility principle to priority of legal substance; the retroactive decision caused legal uncertainly.